2019
DOI: 10.3390/v11121111
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal Activity of Gold Nanoparticles Synthesized by Green Chemistry Using Garlic Extract

Abstract: Measles virus (MeV) is a paramyxovirus that infects humans, principally children. Despite the existence of an effective and safe vaccine, the number of cases of measles has increased due to lack of vaccination coverage. The World Health Organization (WHO) reports that the number of cases worldwide multiplied fourfold between January and March 2019, to 112,000. Today, there is no treatment available for MeV. In recent years, it has been demonstrated that natural extracts (herbal or algal) with antiviral activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 31 publications
0
74
0
Order By: Relevance
“… 211 215 Porous gold nanoparticles provide extensive surface area and more efficiently bind the disulfide bonds 216 and stop the viral infection compared to conventional inorganic nanoparticles ( Figure 10 ). 217 …”
Section: Nanotheranostics Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“… 211 215 Porous gold nanoparticles provide extensive surface area and more efficiently bind the disulfide bonds 216 and stop the viral infection compared to conventional inorganic nanoparticles ( Figure 10 ). 217 …”
Section: Nanotheranostics Perspectivementioning
confidence: 99%
“…The porous gold nanoparticles provide larger surface area for the breakage of disulfide bond. Adapted from ref ( 217 ).…”
Section: Nanotheranostics Perspectivementioning
confidence: 99%
“…A well-known example of this property is silver nanoparticles that have been shown to possess antiviral activity against HBV, HIV, and influenza virus [127,128]. Also, gold nanoparticles have demonstrated substantial virucidal activity against the measles virus presenting them as a possible candidate for the prevention and treatment of enveloped viruses [129]. Moreover, nanoparticles provide a platform for optimization of drug dosing and augmentation of drug delivery through enhanced stability and prolonged drug retention times [130,131].…”
Section: Resveratrolmentioning
confidence: 99%
“…Pre-clinical investigations ( in-vitro and in-vivo ) of garlic extract (GE) and its OSCs have shown antiviral activity against a wide range of viral infections including flu and respiratory infections ( Chavan et al, 2016 ; Chen et al, 2011 ; Choi, 2018 ; Liu et al, 2013 ; Mehmood et al, 2018 ; Mehrbod et al, 2009 ; Mehrbod et al, 2013 ; Mohajer Shojai et al, 2016 ; Rasool et al, 2017 ; Tsai et al, 1985 ; Weber et al, 1992 ), immunosuppression (“ Garlic extract for HIV? ", 1998 ; Kun Silprasit et al, 2011 ; Shoji et al, 1993 ; Tatarintsev et al, 1992 ; Walder et al, 1997 ), genital herpes ( Romeilah et al, 2010 ; Weber et al, 1992 ), neurological infections ( Luo et al, 2001 ; Meléndez-Villanueva et al, 2019 ; Wang et al, 2016 ), gastrointestinal infections ( Al-Ballawi et al, 2017 ; Weber et al, 1992 ), plant infections ( Mohamed, 2010 ; Shyam & Ashish, 2011 ; Wang et al, 2020 ) and others ( Liu et al, 2013 ; Seo et al, 2017 ; Wang et al, 2017 Weber et al, 1992 ) ( Table 3 , Table 4 ). Further, randomized clinical trials on different commercial garlic preparations also showed that garlic plays a significant therapeutic role in various viral infections such as cold and flu, viral-induced hepatitis, viral-associated warts, as well as immune enhancing activity in viral infected patients ( Table 5 ).…”
Section: Introductionmentioning
confidence: 99%